Comparative Analysis of Putative Prognostic and Predictive Markers in Neuroblastomas: High Expression of PBX1 Is Associated With a Poor Response to Induction Therapy - Veselska, Renata; Jezova, Marta; Kyr, Michal; Mazanek, Pavel; Chlapek, Petr; Dobrotkova, Viera; Sterba, Jaroslav (Frontiers in Oncology, 2019)
The survival rate for patients with high-risk neuroblastomas remains poor despite new improvements in available therapeutic modalities. A detailed understanding of the mechanisms underlying clinical responses to multimodal treatment is one of the important aspects that may provide precision in the prediction of a patient’s clinical outcome. Our study was designed as detailed comparative analysis of five selected proteins (DDX39A, HMGA1, HOXC9, NF1, and PBX1) in one cohort of patients using the same methodical approaches. These proteins were already reported separately as related to the resistance or sensitivity to retinoids and as useful prognostic markers of survival probability. In the cohort of 19 patients suffering from high-risk neuroblastomas, we analyzed initial immunohistochemistry samples obtained by diagnostic biopsy and postinduction samples taken after the end of induction therapy. The expression of DDX39A, HMGA1, HOXC9, and NF1 showed varied patterns with almost no differences between responders and nonresponders. Nevertheless, we found very interesting results for PBX1: nonresponders had significantly higher expression levels of this protein in the initial tumor samples when compared with responders; this expression pattern changed inversely in the postinduction samples, and this change was also statistically significant. Moreover, our results from survival analyses reveal the prognostic value of PBX1, NF1 and HOXC9 expression in neuroblastoma tissue. In addition to the prognostic importance of PBX1, NF1 and HOXC9 proteins, our results demonstrated that PBX1 could be used for the prediction of the clinical response to induction chemotherapy in patients suffering from high-risk neuroblastoma.